The Imperial War Museum Book of the Desert War - Edited by Bramall, Lord and Gilbert, Adrian (London Sidgwick & Jackson, 1992)
The extracts from memoirs, diaries, letters and interviews reflect the experience of the campaign, from the noise and smoke of battle and the vagaries of desert life to leave spent in Cairo and Alexandria, the development of the Long Range Desert Group and the SAS, Rommel and the Afrika Corps.
Includes Index and Illustrations.
Keywords: World War, 1939-1945 -- Campaigns -- Africa, North